A COMPARATIVE STUDY ON VARNASAMAMNAYA-VARNOCCARANAVIDHI BETWEEN RIKPRĀTIŚĀKHYA AND VAJASANEYIPRATISHAKHYA - Das, Arpita; Pandey, Laxminarayan (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Sanskrit is the oldest heart-grabbing language in the world, flawless, endowed with all the required rituals, endowed with all the parts of literature, poetry, dictionary, grammar and others. It is divided into two parts by the difference between Vedic and Sanskrit. Their Vedic language is the oldest. The sages have indeed explained the fourfold nature of the Vedas by distinguishing them from the Ṛg, Sāma, Yajur and Atharva Vedas. According to the śruti, the sixfold Veda is to be studied and understood by a brāhmaṇa as the causeless religion, and the sixfold Veda is to be studied and understood. The limb is the name of the benefactor. These are the limbs that are known as the limbs. The things which help in understanding the nature of the Vedas are called the limbs. There are six parts of the Vedas. They are – Shiksha, Kalpa, Grammar, Nirukta, Chhanda and Jyoti. It is said that the education is the Kalpa, and the grammar is the Nirukta, and the chandas are the Vedas. There are also six parts of the Vedas called Jyotishamayana so far . Although the Pratiśākhya does not appear to be included in the six Vedic literatures, it is safe to say that this work is as indispensable in the world of Vedic literature as the educational Vedic literature. The Pratiśākhya text also gives knowledge of the verse, syllable, pronunciation process, vowels, etc. of the Vedic mantra. There are many Pratishakhya texts according to the branches of the Prativeda. For example – a) Rigveda-Pratishakhya under the Shakala branch of the Rigveda b) Riktantra under the Kothuma branch of the Samaveda c) Taittiriyapratishakhya under the Taittiriya branch of the Krishna Yajurveda d) Vajsaneyipratishakhya under the Madhyandina branch of the Shukla Yajurveda e) Atharvaveda The four chapters of the Śaunakīya, etc. Although there appears to be unity in the name, Pratiśākhya, the Vedas are separate. Therefore, the subject of this research paper is a comparative review of the Vajasaneyi Pratishakhya of the Madhyandina branch of the Shukla Yajurveda with the Rigveda Pratishakhya of the Shakala branch of the Rigvega.